Human epidermal cell cultures: growth and differentiation in the absence of differentiation in the absence of dermal components or medium supplements. - Eisinger, M (1979)
Human epidermal cells grew and differentiated in vitro, provided that the pH of the culture medium was at 5.6-5.8, the seeding density was optimal (approximately 2.5 x 10(5) cells per cm2), and the incubation temperature was maintained at 35-37 degrees C. Under these conditions, epidermal cells from many different skin locations grew to confluency within 15-20 days and formed multi-layered sheets whose differentiated structure resembled that of the full depth of skin epidermis. Cell proliferation and differentiation did not require a feeder layer, a collagen substrate, a high concentration of fetal bovine serum, or added hormones. The sheets of differentiated epidermal cells could be dissociated from the plastic surfaces of the tissue culture flasks. The use of such cultured cells for wound dressing is proposed.